Intra-ply yarn sliding defect in hemisphere preforming of a woven preform. (April 2018) - Labanieh, Ahmad Rashed; Garnier, Christian; Ouagne, Pierre; Dalverny, Olivier; Soulat, Damien
Abstract: Preforming is the first step to manufacture a complex composite part via Liquid Composite Moulding processes. The defects that may be encountered during this phase within the preform architecture may decrease the expected mechanical performances of the final part. The intra-ply yarn sliding is a defect frequently observed during preforming of a woven preform but its mechanism is far from being fully understood. The aim of this study is to analyse the mechanism of this defect arising when preforming of a carbon woven fabric into hemispheric shape. An experimental study followed by analytical analysis was performed to evaluate the effect of the process parameters, material properties and ply configuration conditions on the yarn tension and contact stresses. A significant effect of the yarn tension and the contact shear stresses on the defect occurrence was demonstrated. Based on this analysis, solutions were tested with success to prevent this defect.